1996
DOI: 10.1177/104063879600800121
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Serotypes and Strains of Streptococcus Suis in Naturally Infected Swine Herds

Abstract: Streptococcus suis is a cause of pneumonia, meningitis, and arthritis in swine. 2,5,11,16 The identification of S. suis in swine herds is increasing, and anecdotal field reports of difficulty in disease control and management, especially "vaccine failure," are common. The importance of S. suis as a primary pulmonary pathogen is controversial because of the difficulty in experimentally reproducing the disease. A retrospective study of porcine cases of S. suis submitted to the Indiana Animal Disease Diagnostic L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 14 publications
(17 reference statements)
0
15
0
2
Order By: Relevance
“…Similarly, in our study only 16 of 40 S. suis isolates from pigs with pneumonia were isolated as pure cultures. In agreement with the current knowledge of the pathogenicity of S. suis (14,18,24), we therefore assumed that the isolates from pigs with typical signs (i.e., meningitis, etc.) represented the most virulent strains, whereas isolates from pigs with pneumonia were less invasive and, thus, less virulent.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Similarly, in our study only 16 of 40 S. suis isolates from pigs with pneumonia were isolated as pure cultures. In agreement with the current knowledge of the pathogenicity of S. suis (14,18,24), we therefore assumed that the isolates from pigs with typical signs (i.e., meningitis, etc.) represented the most virulent strains, whereas isolates from pigs with pneumonia were less invasive and, thus, less virulent.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast to the importance of S. suis as a primary pathogen in pigs with meningitis, septicemia, or arthritis, it's causative role in pneumonia is not as clear since in many cases S. suis is isolated together with other lung pathogens such as Pasteurella spp., B. bronchiseptica, or Mycoplasma spp. (18,24). Similarly, in our study only 16 of 40 S. suis isolates from pigs with pneumonia were isolated as pure cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as S. suis is often isolated from the lungs of pigs with pneumonia along with other agents potentially involved in respiratory disease (such as Pasteurella multocida, Haemophilus parasuis, Actinobacillus pleuropneumoniae, swine influenza virus, B. bronchiseptica, and Mycoplasma spp. [22,28,38]), the role of S. suis in pneumonia remains somewhat controversial. Although S. suis is isolated in pure culture from pneumonia with reasonable frequency (1,22) further epidemiological studies are required to address the etiological role of S. suis in porcine pneumonia and the particular clones involved.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, it was found that pigs can be infected with multiple serotypes of S. suis (15,17). These findings may account in part for the difficulty in disease control by vaccines.…”
Section: Vol 40 2002 S Suis Multiplex Pcr Assays 2927mentioning
confidence: 99%